Takedown twenty - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2013)
New Jersey bounty hunter Stephanie Plum knows better than to mess with family. But when powerful mobster Salvatore "Uncle Sunny" Sunucchi goes on the lam in Trenton, it's up to Stephanie to find him. Uncle Sunny is charged with murder for running over a guy (twice), and nobody wants to turn him in--not his poker buddies, not his bimbo girlfriend, not his two right-hand men, Shorty and Moe. Even Trenton's hottest cop, Joe Morelli, has skin in the game, because "just Stephanie's luck" the godfather is his actual godfather. And while Morelli understands that the law is the law, his old-world grandmother, Bella, is doing everything she can to throw Stephanie off the trail.